From being born to being technological. The bioethical revolution of Peter Sloterdijk - Della Torre, Cecilia (Medicina e Morale, 2019)
The origin of the human being has always been identified with human generation. Nowadays, with the introduction of new technologies, reproduction is changing completely, taking on new features. This change involves a radical re-formulation of the anthropological perspective connected to the domain of "nativity". Through an analysis of Peter Sloterdijk's thought, this article explores the overturning of the reference model: instead of considering the human being as son, the model sees it as a technical product. This study focuses in particular on the changes made by Sloterdijk to the lexicon linked to the thematic area of "generation", with the aim of showing how the "motherson" terms are used with a completely distorted meaning. The goal is to analyse and evaluate Sloterdijk's anthropological revolution, so as to expose the theoretic contradictions of the proposed paradigm shift.